Community Service Programs and Cultural Resilience: Revitalizing Indigenous Knowledge Systems - Rashid Rahman; Zain Nizam; Rina Farah; Nur Azizah (Pengabdian: Jurnal Abdimas, 2026)
Indigenous knowledge systems represent vital cultural resources that sustain community identity, social cohesion, and adaptive capacity, yet they face increasing erosion under the pressures of modernization and standardized development practices. Community service programs have been widely implemented as instruments of social engagement, although their role in strengthening cultural resilience and revitalizing indigenous knowledge remains insufficiently examined. This study aims to analyze how community service programs contribute to cultural resilience through the revitalization of indigenous knowledge systems within local communities. The research employs a qualitative approach grounded in participatory and interpretive frameworks, combining in-depth interviews, participant observation, and analysis of community service program documents. The findings reveal that community service programs foster cultural resilience when they are designed as participatory processes that recognize indigenous knowledge holders as central actors. Such programs facilitate intergenerational knowledge transmission, strengthen cultural pride, and support the adaptation of traditional practices to contemporary contexts. The results also indicate that cultural revitalization extends beyond preservation, functioning as an active process embedded in everyday social life. The study concludes that community service programs can serve as effective platforms for sustaining indigenous knowledge systems when they emphasize reciprocity, local agency, and cultural authority. These findings underscore the importance of culturally responsive community engagement in promoting sustainable and resilient development.